Wisteria floribunda Agglutinin-Positive Mac-2 Binding Protein as a Screening Tool for Significant Liver Fibrosis in Health Checkup - Tamaki, Nobuharu; Kurosaki, Masayuki; Takahashi, Yuka; Itakura, Yoshie; Kirino, Sakura; Inada, Kento; Yamashita, Koji; Sekiguchi, Shuhei; Hayakawa, Yuka; Osawa, Leona; Higuchi, Mayu; Takaura, Kenta; et al. (International journal of molecular sciences, 2020)
Chronic liver disease is generally widespread, and a test for screening fibrotic subjects in a large population is needed. The ability of Wisteria floribunda agglutinin-positive mac-2 binding protein (WFA+-M2BP) to detect significant fibrosis was investigated in health checkup subjects in this research. Of 2021 health checkup subjects enrolled in this prospective cross-sectional study, those with WFA+-M2BP ≥ 1.0 were defined as high risk. Liver fibrosis was evaluated using magnetic resonance elastography (MRE) in subjects with high risk. The primary outcome was the positive predictive value (PPV) of WFA+-M2BP for significant fibrosis (liver stiffness ≥ 2.97 kPa by MRE). This trial was registered with the UMIN clinical trial registry, UMIN000036175. WFA+-M2BP ≥ 1.0 was observed in 5.3% of the 2021 subjects. The PPV for significant fibrosis with the threshold of WFA+-M2BP at ≥1.0, ≥1.1, ≥1.2, ≥1.3, ≥1.4, and ≥1.5 was 29.2%, 36.4%, 43.5%, 42.9%, 62.5%, and 71.4%, respectively. A WFA+-M2BP of 1.2 was selected as the optimal threshold for significant fibrosis among high-risk subjects, and the PPV, negative predictive value, sensitivity, and specificity for significant fibrosis were 43.5%, 84.0%, 71.4%, and 61.8%, respectively. WFA+-M2BP ≥ 1.2 was significantly associated with significant fibrosis, with an odds ratio (OR) of 4.04 (95% confidence interval (CI): 1.1–16, p = 0.04), but not FIB-4 ≥ 2.67 (OR: 2.40, 95%CI: 0.7–8.6, p-value = 0.2). In conclusion, WFA+-M2BP is associated with significant fibrosis and could narrow down potential subjects with liver fibrosis. The strategy of narrowing down fibrosis subjects using WFA+-M2BP may be used to screen for fibrotic subjects in a large population.